Practices in Power System Management in India - Raja, J. (Power Systems,, 2018)
This book presents the state-of-the-art methods and procedures necessary for operating a power system. It takes into account the theoretical investigations and practical considerations of the modern electrical power system. It highlights in a systematic way the following sections: Power Sector Scenario in India, Distribution Planning and Optimization, Best practices in Operation & Maintenance of Sub-Transmission & Distribution Lines, Best Practices in Operation and Maintenance of Distribution Substation Equipment's and Auxiliaries, Best Practice in Operation & Maintenance of Transformer and Protection Systems, International Best Practices in Operation & Maintenance (Advanced Gadgets), Aerial Bunch Conductor (ABC) based Distribution System, Best Practices in Operation & Maintenance of Energy Meters.